A complete ab initio thermodynamic and kinetic catalogue of the defect chemistry of hematite α-Fe2O3, its cation diffusion, and sample donor dopants. Issue 45 (11th November 2021) - Shousha, Shehab; Khalil, Sarah; Youssef, Mostafa
Abstract : This paper studies comprehensively the defect chemistry of and cation diffusion in α-Fe2 O3 . Abstract : This paper studies comprehensively the defect chemistry of and cation diffusion in α-Fe2 O3 . Defect formation energies and migration barriers are calculated using density functional theory with a theoretically calibrated Hubbard U correction. The established model shows a good agreement with experimental off-stoichiometry and cation diffusivities available in the literature. At any temperature, and are the predominant ionic defects in hematite at the two extremes of oxygen partial pressure ( p O2 ) range, reducing and oxidizing, respectively. Between these two extremes, an intrinsic electronic regime exists where small polaronic electrons and holes are the dominant charge carriers. The calculated migration barriers show that Fe ions favor the diffusion along the 〈111〉 direction in the primitive cell through an interstitial crowdion-like mechanism. Our model suggests that cation diffusion in hematite is mainly controlled by the migration of, while may contribute to cation diffusion at extremely low p O2 . Our analysis in the presence of two sample donor dopants Ti and Sn indicates that high temperature annealing at T > 1100 K is needed to prepare n-type hematite at ambient p O2, consistently with prior experimental findings. Alternatively, annealing at lower temperatures requires much lower p O2 to avoid compensating the donors with Fe vacancies. A synergistic comparison of our theoretical model and the experimental results on Ti-doped hematite led us to propose that free electrons and small polarons coexist and both contribute to n-type conductivity. Our validated model of defective hematite is a foundation to study hematite in applications such as corrosion and water splitting.